Hudson's Bay Company store - (Author); (Interviewer); (Publisher) (1900)
The first Hudson's Bay store and warehouses were near the river, Athabasca, Alberta. Left to right: Leslie Wood (manager), Jock Irwin (handyman), Russell E. Bannerman (clerk).